Learning about architecture: The act of making and being - MackIntosh, Lara; Phillips, M. (2017)
© Common Ground Research Networks, Lara Mackintosh, Lara Mackintosh, All Rights Reserved.Internationally, design-build programs within architectural education have a long and successful history, and yet the teaching practices and learning outcomes embedded within these programs are still considered innovative. Such programs, while increasing in number, have yet to be integrated within mainstream architectural education, despite their broad reaching and long lasting outcomes. A key component of these programs is the critical reflection that takes as part of the design process, during construction and once the project is inhabited. This paper builds on the authors' experiences of and within a number of design-build programs and discusses the role of critical reflection in the learning experience. A model for a framework of architectural pedagogy is being developed to support transformative experiences in architectural learning. Design-build programs provide diverse opportunities for those involved to understand each other and develop a sense of self and identity. This understanding, realised through the sharing of experience of making and being in place, challenges the beliefs and values of those involved, and has the potential to prompt, support and sustain socially and environmentally responsible architectural practices.